Electrodeposition of Nickel Tin Selenide Thin Film - Abd Rahim, Kartini (2003)
Nickel tin selenide thin films have been potentiostatically electrodeposited on titanium substrate from aqueous solution consisting of nickel sulphate (NiSO4), tin chloride (SnCl2) and sodium selenide (Na2SeO3). Ethylenediaminetetraacetic acid (EDTA) was used as additive to improve the quality of deposit and longevity of the deposition bath. The electrodeposition potential was selected from the cyclic voltammetry (CV) experiment. The crystalline structure, morphology, composition and photoactivity of the films deposited were characterised by using X-ray diffractometry (XRD), scanning electron microscopy (SEM), energy disperse analysis of X-rays (EDAX) and linear sweep photovoltammetry (LSPV). X-ray photoelectron spectroscopy (XPS) was performed to the selected sample. The band gap energy and type of optical transition were determined from optical absorbance data.